A guided particle swarm optimization algorithm for nurse scheduling problem - Mohd Rasip, Norhayati; Hasan Basari, Abd Samad; Hussin, Burairah; Ibrahim, Nuzulha Khilwani (Hikari Ltd, 2014)
The Nurse Scheduling Problem (NSP) is a combination of optimization problem and important management functions performed by nurses which directly affected the hospital services and the patient care . The NSP is varied which tends to be solved with nature inspired search approaches such as particle swarm optimization (PSO). Hence, the main purpose of this paper is to utilize the PSO to find the balance of nurse assignment by considering the coverage demand and nurse preferences. The actual task of generating the nurse schedule is investigated in ad, and H. Basari, “An Investigation of. The proposed algorithms are tested on the real data and the obtained results demonstrate that the proposed particle swarm optimization has better performance to cope with complex scheduling problem. The experimental results show that the guided randomly PSO algorithm is more effective in term of the time constraint and the feasible assignment solution.